Expression Profile Analysis of Selenium-Related Genes in Peripheral Blood Mononuclear Cells of Patients with Keshan Disease. (17th November 2019) - Liu, Xiaojuan; He, Shulan; Peng, Juanxia; Guo, Xiong; Tan, Wuhong
Abstract : Keshan disease (KD) is an endemic cardiomyopathy, which mainly occurs in China. Selenium deficiency is believed to play an important role in the pathogenesis of KD, but the molecular mechanism of selenium-induced damage remains unclear. To identify the key genes involved in selenium-induced damage, we compared the expression profiles of selenium-related genes between patients with KD and normal controls. Total RNA was isolated, amplified, labeled, and hybridized to Agilent human 4 × 44 K whole genome microarrays. Selenium-related genes were screened using the Comparative Toxicogenomics Database. The microarray data were subjected to single-gene and gene ontology (GO) expression analysis using R Studio and Gene Set Enrichment Analysis (GSEA) software. Quantitative real-time PCR was conducted to validate the microarray results. We identified 16 upregulated and 11 downregulated selenium-related genes in patients. These genes are involved in apoptosis, metabolism, transcription regulation, ion transport, and growth and development. Of the significantly enriched GO categories in KD patients, we identified four apoptosis-related, two metabolism-related, four growth and development-related, and four ion transport-related GOs. Based on our results, we suggest that selenium might contribute to the development of KD through dysfunction of selenium-related genes involved in apoptosis, metabolism, ion transport, and growth and development in the myocardium.